Economic Diversification through Knowledge-Based Industries 2024 - Mohammed , Halima Younis Abbas (Journal of Ecohumanism, 2024)
This study aims to analyze the impact of the knowledge economy on economic diversification in Saudi Arabia and its contribution to sustainable development by developing supportive strategies and policies. To achieve this goal, the study employed an inductive approach, gathering data and information from diverse sources, including books, references, and both Arabic and international journals. Descriptive and analytical economic analyses were used to review and interpret data related to knowledge economy indicators. Additionally, statistical analysis was conducted using EViews software to examine regression relationships between independent and dependent variables, aiming to evaluate the knowledge economy’s role in promoting economic diversification and sustainable development in Saudi Arabia. The study found that the knowledge economy plays a pivotal role in enhancing economic diversification. The results showed that regions focusing on knowledge-based industries exhibit higher levels of productivity, technological advancement, and employment in high-skill sectors. Investments in education, research, and development significantly bolstered the competitiveness of these industries in the global market, thereby supporting sustainable economic growth. Analysis results also revealed that economic diversification positively supports the growth of knowledge-based industries, particularly in Saudi Arabia, where diversification efforts have reduced reliance on traditional sectors and enhanced the economy’s resilience and adaptability to global changes.